KONGLOMERASI MEDIA MEMPERKUAT HEGEMONI PENGUASA DAN OLIGARKI PADA ERA NEW MEDIA - Ludhy Cahyana (AT-TAWASUL, 2022)
Media conglomeration is a real form of media political economy, where the commodification of information becomes a very profitable business. However, lately the media business is also hobbled to face an advertising tariff war with social media. However, the closeness of the big media owners with the power circle makes the media only as a tool to receive concessions or rewards that benefit the media owner's business. Thus, revenue from advertising can be excluded, but other businesses are still on the way to sustain their media business. This relationship also encourages the growth of the media with reporting that is not critical of the abuses of power by the government and their cronies. Even the media is a tool to strengthen the hegemony of power that works as soft power to cut people's critical reasoning